Effects of Hole Diameter on Torsional Mechanical Properties of the Rabbit Femur - Massie, Anna M.; Kapatkin, Amy S.; Garcia, Tanya C.; Guzman, David Sanchez-Migallon; Chou, Po-Yen; Stover, Susan M. (Veterinary and Comparative Orthopaedics and Traumatology, 2019)
Objective The aim of this study was to evaluate and compare the effect of three clinically applicable screw hole diameters on rabbit femoral torsional structural properties.Sample Eighteen pairs of skeletally mature New Zealand White rabbit femora (36 bones).Materials and Methods Femora with a bicortical hole at mid-diaphysis from one of the 3-drill bit sizes, 1.1 mm, 1.5 mm, 2.0 mm, and intact bones were studied. Each bone was bi-axially loaded in a servo-hydraulic load frame with the bone positioned so the neutral axis of torsion was aligned with the centre of the bone diaphysis. Axial compression to 35% body weight was applied to represent compression at stance, and rapid external torsion was applied to failure. Torque and angular deformation data were plotted for each test, with pre-yield and post-yield stiffnesses derived. Yield and failure torques and angles were determined, along with calculated yield, failure and post-yield energies.Results Failure torque was reduced compared with that of intact bone; weakened by 37% in 1.1-mm hole models, 53% in 1.5-mm hole models and 65% in 2.0-mm hole models. The torque angular deformation curves lacked plastic deformation.Conclusions and Clinical Relevance This study demonstrates the unique, brittle biomechanics of rabbit bone. Based on data from other species that strength loss of no more than 50% is acceptable when placing orthopaedic implants, no defect greater than 1.1 mm (15% bone diameter) is recommended in rabbit femora.
Keywords: mechanical properties; rabbit bone; torsional properties; drill hole